Kinetic Study of Oxidation of Thiophene-2-Carbaldehyde by Imidazolium Dichromate Promoted By 1, 10-Phenanthroline (International Journal of Scientific Research in Science and Technology, 2024)
Kinetic study of oxidation of Thiophene-2-carbaldehyde by Imidazolium dichromate in aqueous acetic acid medium using 1,10-phenanthroline have been studied. In the absence of mineral acids, the oxidation kinetics of Thiophene-2-carbaldehyde acid by Imidazolium dichromate shows a first-order dependence on Imidazolium dichromate and fractional order on Thiophene-2-carbaldehyde. The variation of ionic strength, H+ and reaction product have in significant effect on reaction rate. Activation parameters have been studied for the reaction from the Arrhenius plot by studying the reaction at different temperatures.